Secondary sclerosing cholangitis in critically ill patients: Model of End-Stage Liver Disease score and renal function predict outcome - Voigtländer, T.; Negm, A. A.; Schneider, A. S.; Strassburg, C. P.; Manns, M. P.; Wedemeyer, J.; Lankisch, T. O. (Endoscopy, 2012)
Secondary sclerosing cholangitis in critically ill patients (SSC – CIP) is an underdiagnosed emerging disease. The aim of this study was to characterize clinical features and prognostic factors for mortality in SSC – CIP. This retrospective study included 54 patients who were diagnosed via endoscopic retrograde cholangiopancreatography (ERCP) after cardiothoracic surgery (n = 21), sepsis (n = 13), polytrauma (n = 11), and others (n = 9). In total, 33 patients who either died (n = 27) or needed liver transplantation (n = 6) were compared with surviving patients (n = 21). The model for end-stage liver disease (MELD) score and need for renal replacement therapy were independent risk factors for mortality. Compared with ERCP, accuracy was 30 % for ultrasound and 36 % for liver biopsies. As a result of microbiological bile analysis, 28 % of patients required a change in antibiotic treatment. SSC – CIP is frequently a fatal disease. ERCP should be considered in selected patients to establish the diagnosis and hence provide useful clinical information.